Building brand protection strategy in contemporary enterprises - Sałamacha, Anna (Budowanie strategii ochrony marki we współczesnych przedsiębiorstwach, 2020)
The aim of this paper is to present comprehensive solutions in the field of brand protection against the actions of dishonest imitators. First, the brand elements important from the its protection point of view were identified, i.e. physical product with packaging and/or service, visual identification system and intangible (‘soft’) brand elements. Then the methods for determining the brand protection status were described. The brand protection status study consists in a diagnosis of the brand life cycle phase and of the implemented brand protection tools. Next the method of examining the state of the existing and potential violations in the form of the designed early warning system against imitation was presented. Finally, the model procedure of the brand protection strategy was proposed. It provides guidelines for the creation, selection and implementation of the strategies, both preventive and corrective
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 87-100